MECHANISMS OF THE INFLUENCE OF COPPER ON THE REPRODUCTIVE ABILITY OF MALES - Usenko, S.; Siabro, A. (Scientific Progress & Innovations, 2022)
The article highlights data on the influence of copper on physiological processes in the animal body in particular on the formation of sexual function, through the activity of enzymes and the synthesis of hormones. The purpose of the review was to reveal the mechanisms of copper's influence on the functioning of biological systems that shape the reproductive function of males. It has been established that the leading role of copper in physiological and biochemical processes is due to its essentiality. Males have homeostatic mechanisms for regulating copper metabolism including the chaperone proteins CCS, COX17, and ATOX1, which ensure the transport of this element, and the proteins ATP7A and ATP7B, the main function of which is to maintain an optimal copper level. Mutations in the genes encoding ATP7A and ATP7B proteins cause genetic disorders of copper metabolism, in which its deficiency or excess in the body is noted. Both an increase and a decrease in the supply of copper to the genital organs of males lead to histological changes in the testicles and disruption of spermatogenesis processes. Due to its redox properties, copper is a cofactor of superoxide dismutase and cytochrome coxidase, which are closely related to the functional activity of spermatozoa. By catalyzing the dismutation of superoxide anions, superoxide dismutase protects spermatozoa from the negative effects of free radicals during their maturation during passage through the epididymis. Due to its leading role in oxidative phosphorylation, cytochrome c-oxidase maintains a normal level of ATP, which is necessary at all stages of spermatogenesis and ensures the mobil ity of gametes in the female reproductive tract. The hypothalamic-pituitary-gonadal system supports the normal development and functioning of male reproductive organs throughout life. The interdependence of copper metabolism and adrenal function is related to β-dopamine hydroxylase, which stimulates the synthesis of norepinephrine. This catecholamine, acting as an important neurotransmitter, affects the synthesis of steroid hormones in the testicles, which enables the normal development of the genitals. Cop per contributes to the contraction of blood vessels and smooth muscles of the cavernous body; norepinephrine causes penile detumescence, which is an integral part of the bilateral system of erectile function. Given the leading role of copper in the differentiation, maturation, and proliferation of leukocytes, this element is necessary to support the immune system. Leukocytes are involved in phagocytosis and activation of the respiratory burst, which may be a key factor in sperm damage in the female genital tract. Therefore, being in a close relationship with the hypothalamic-pituitary system, copper regulates the manifestation of sexual reflexes, and supports the quality of sperm production, capacitation, and fertilization processes.